Presence of accounting qualitative charecteristics information in candidates accountability by the federal deputy candidates of Federal District in 2014 elections (Revista Brasileira de Contabilidade e Gestão, 2016)
One of the Accounting objectives is to ensure the quality information for decision-making of its various users in a useful way, being this a mechanism for which there is transparency in the actions, based on the qualitative characteristic of faithful representation, relevance, understandability, comparability, timeliness and verifiability . Thus, this study seeks to analyze the accountability of candidates for federal deputy for the Federal District in the 2014 elections with respect to these characteristics to examine its transparency. Thus, it is made a prospectus of elections in Brazil, a review of the Brazilian electoral legislation and literature that are listed definitions and discussions made by scholars of the subject. The method used was exploratory and descriptive, it is done using the description of features envisioned with the documentary analysis of digital services delivered to the Superior Electoral Court by applicants. Thus, it was concluded that the qualitative characteristics are hampered by a lack of important information that can influence the user's decision-making, thereby undermining its transparency.
Keywords: 2014 elections; qualitative characteristics of accounting information; accounting information; transparency